Uterus histomorphometry of alpacas (Vicugna pacos) in induced luteal phase, with GnRH or copulation. - Goicochea-Vargas, J. (2024)
Background: Alpacas have reproductive traits such as induced ovulation and a higher gestation rate in the left uterine horn (LUH). Additionally, low fertility and high embryonic mortality are significant challenges in alpaca breeding. To address these issues, it is essential to study the histological changes occurring in the uterine wall during day 8 of the luteal phase (LP). Aim: This research aims to describe these changes in alpacas with induced ovulation using GnRH or copulation. Methods: The study was conducted on 8 sexually mature fertile alpacas with a preovulatory follicle of ≥ 7 mm. Ovulation was induced with GnRH (G1, n = 3) and natural mating' (G2, n = 5), confirmed by ultrasound showing the disappearance of the follicle and formation of the corpus luteum (CL). On day 8 of the LP, samples of the uterine wall from the right and LUHs were obtained through a midline laparotomy. A uterine lavage with PBS was also performed, and no embryo-ova was found. The tissues were fixed, processed, and stained with Hematoxylin and Eosin. Measurements of the myometrium and endometrium, the area of the superficial and deep endometrial glands, the height of the gland cells, and the height of the endometrial mucosal cells were performed using microscopy and software. The measurements were taken in microns (um), from 12 different photographs per animal. Results: In G2 (copulation), greater thickness of the endometrium and myometrium, as well as a larger area of the superficial glands and cell height, were observed (p < 0.005). Additionally, the area of the superficial glands in the left horn was greater compared to the right. Conclusion: The thickness of the myometrium and endometrium, and the area of the superficial glands of the LUH in alpacas during the LP (day 8), induced by copulation (G2), show better development. This research provides new insights into changes in the histomorphometry of the alpacas' uterus during this stage and is the first report on this species.